Artificial intelligence and arms control : what it means for Singapore - Gilli, Andrea (2020)
Arms control can be pursued and applied to the realm of emerging technologies, but it must be narrow in focus to ensure effectiveness and avoid unintended consequences – like hampering relations with the private industry. What are the implications for Singapore?